The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1029/2006jd007947
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical and microphysical properties over the Atlantic Ocean during the 19th cruise of the Research Vessel Akademik Sergey Vavilov

Abstract: [1] This paper presents aerosol optical depths in the total atmospheric column, aerosol size distributions, number concentrations and black carbon mass concentrations at the deck level measured in October

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 35 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The comparison between the range of variation of the aerosol optical depths retrieved by SeaWiFS over our study area and that measured by AERONET Marine Aerosol Network stations was performed here based on the literature. Sakerin et al [2007] and Macke et al [2008] measured aerosol optical depth at 500 nm of about 0.3–0.7 near the West African coast. Such range of values is consistent with that obtained by SeaWiFS in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison between the range of variation of the aerosol optical depths retrieved by SeaWiFS over our study area and that measured by AERONET Marine Aerosol Network stations was performed here based on the literature. Sakerin et al [2007] and Macke et al [2008] measured aerosol optical depth at 500 nm of about 0.3–0.7 near the West African coast. Such range of values is consistent with that obtained by SeaWiFS in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…If the suggested transport pathways from the Atlantic and Indian Ocean are essentially correct, the BC variation at Syowa should be associated with the BC concen-15 tration in the marine boundary layer and the lower free troposphere over the Atlantic and Indian Ocean. Previous ship-borne BC measurements indicated BC concentrations in the range of <10 ng m −3 in January-April over the southern Indian Ocean (<56 • S) (Moorthy et al, 2005), and 20∼80 ng m −3 in October∼December over the Indian Ocean∼Southern Ocean (Sakerin et al, 2007). Ranges of <10∼160 ng m −3 in 20 October∼November and <10∼120 ng m −3 in February∼March were observed over the southern Atlantic Ocean (close to the Southern American continent) -Southern Ocean (Evangelista et al, 2007).…”
Section: Bc Injection Into Syowa Station By Cyclonementioning
confidence: 99%
“…As suggested by Fiebig et al (2009) and Hara et al (2010), EBC is expected to be transported from mid-latitudes and low latitudes. Therefore, EBC mixing states might be changed by aging processes near source regions and during long-range transport (Shiraiwa et al, 2007;Saleh et al, 2013Saleh et al, , 2014Ueda et al, 2018). Indeed, Ueda et al (2018) showed that EBC was present mostly as internal mixtures in the marine boundary layer (MBL) of the Southern Ocean.…”
Section: Variations In Aae At Syowa Station Antarcticamentioning
confidence: 99%